Golongan darah Atlet Sulawesi Selatan Peraih Medali pada PON XIX Tahun 2016 di Jawa Barat - Abdul Rahman; Sarifin G. (Seminar Nasional LP2M UNM, 2019)
Research on the study of the blood types of South Sulawesi athletes at the 2016 PON XIX in West Java. The population in this study were South Sulawesi athletes who won medals in the 2016 PON XIX in West Java using a purposive sampling technique of 23 athletes. This type of research is a type of descriptive research with a blood type survey method. Data from the results of this study were analyzed using the percentage formula. Based on these results, the results obtained from the percentage of blood groups of South Sulawesi athletes who won medals in PON XIX in West Java in 2016 with the number of athletes winning medals as many as 23 athletes, namely Blood Type O, with athletes percentage of 60.87% or 14 medal-winning athletes, Blood Type A with an athlete percentage of 34.78% or 8 medal-winning athletes, AB blood group with an athlete percentage of 4.35% or 1 medal-winning athlete and not a rolling athlete. Based on the results above, it can be concluded that the group that is more dominant in South Sulawesi athletes who won medals in the 2016 PON XIX in West Java is blood type O (14 athletes) and blood group A (8 athletes).